A comparative study of sodium/hydrogen titanate nanotubes/nanoribbons on destruction of recalcitrant compounds and sedimentation. (1st April 2017) - Kiatkittipong, Kunlanan; Assabumrungrat, Suttichai
Abstract: The performances of sodium titanate nanotubes (Na-TT), hydrogen titanate nanotubes (H-TT), sodium titanate nanoribbons (Na-TR) and hydrogen titanate nanoribbons (H-TR) on adsorption, photodegradation of methylene blue (MB) and sedimentability were investigated. The intrinsic property of Na-TT with high hydroxyl groups (anionic) provided a strong electrostatic interaction between the MB (cationic) under dark condition. The equilibrium and kinetic adsorption were fitted with Langmuir isotherm models and the pseudo-second-order model, respectively. That is, Na-TT showed the best maximum adsorption capacity of 178.6 mg/g and adsorption kinetics of 0.119 g/mg·min. When the light is turned on, H-TT showed advance its photocatalytic reaction rate of 1.16 × 10 −2 min −1 compared with Na-TT (the reaction rate of 1.02 × 10 −2 min −1 ). This attributed the saturated MB adsorption on Na-TT obstructed capacity to absorb photons, and thus the reaction gradually occurred. For the separation of photocatalysts from the suspension by adding alum as coagulant, Na-TT afforded the best sedimentability of which remaining Na-TT in water was approximately 5%. This study demonstrates that adsorption, degradation and sedimentability were governed by the surface area and crystal structure, which revealed increasing the performance in the order TiO2 < H-TR < Na-TR < H-TT < Na-TT. Highlights: TiO2 hydrothermal yield a high surface area titanate nanotubes, TT and ribbons, TR. TT outperformed TR and TiO2 for methylene blue (MB) adsorption and degradation. The presence of Na + ions intercalated in titanate is beneficial for MB adsorption. Particle separability by sedimentation are different among sphere, tube and ribbon. The overall performance are in the order TiO2 < H-TR < Na-TR < H-TT < Na-TT.